2022
DOI: 10.3917/cep1.081.0109
|View full text |Cite
|
Sign up to set email alerts
|

4. On the Rationale of Central Bank Transparency, Accountability and Communication

Abstract: Depuis quelques décennies, la recherche économique sur la transparence, la responsabilité et la communication des banques centrales s’est fortement développée. La conception actuelle des banques centrales a abandonné l’hypothèse d’une « boîte noire muette ». Dès lors que les banques centrales ont pris leur distance à l’égard d’une politique « de mystique et d’énigme monétaire » (Goodfriend, 1986), elles ont adopté un large spectre de stratégies et de méthodes de communication dans le but d’éclaircir leurs acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Trabelsi and Hichri (2021), for example, demonstrated that convergence to equilibrium in the fragmented information game is driven by reinforcement and belief-based learning. 10 Policy implications from the findings suggest that central banks should adopt a subtle transparency approach, recognizing its limitations, and ensuring communication strategies are adaptable to changing economic conditions (Muchlinski, 2022). Whenever there are threats to financial stability such as the crisis times, it would be impartial to opt for partial transparency provided by a fragmented information policy.…”
Section: Discussionmentioning
confidence: 99%
“…Trabelsi and Hichri (2021), for example, demonstrated that convergence to equilibrium in the fragmented information game is driven by reinforcement and belief-based learning. 10 Policy implications from the findings suggest that central banks should adopt a subtle transparency approach, recognizing its limitations, and ensuring communication strategies are adaptable to changing economic conditions (Muchlinski, 2022). Whenever there are threats to financial stability such as the crisis times, it would be impartial to opt for partial transparency provided by a fragmented information policy.…”
Section: Discussionmentioning
confidence: 99%